Orchid Biochemistry 2.0 - Chen, Jen-Tsung (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint is a printed version of the Special Issue, entitled "Orchid Biochemistry 2.0", one literature review, and nine original research articles were published, and the Special Issue provides further insight into several critical subtopics, including reproduction biology, functional genomics in secondary metabolites, as well as polysaccharides and orchid mycorrhizae.